Multidisciplinary applications of deep learning-based artificial emotional intelligence - Chowdhary, Chiranji Lal 1975- (IGI Global, 2023)
This book explores artificial intelligence applications in emotional intelligence including machine learning and deep learning and presents up-to-date technologies and solutions to the main aspects regarding the applications of artificial intelligence in emotional intelligence applications.
Keywords: Affect (Psychology) -- Computer simulation; Artificial intelligence -- Industrial applications; Emotional intelligence; Deep learning (Machine learning)